Aedes aegypti Entomology Index and Environmental Determinants as the Basis for Dengue Fever Control in Bengkulu City - Kermelita, Deri (Health & Medical Sciences, 2025)
Dengue fever continues to be a significant public health issue in Indonesia, with Bengkulu City classified as an endemic area. The transmission of dengue is highly influenced by the density of Aedes aegypti vectors and environmental factors that support their breeding and survival. This study aimed to evaluate the level of Aedes aegypti larval infestation and adult mosquito density as the basis for assessing dengue transmission risk and to analyze the relationship between environmental factors and larval presence in the working area of Sawah Lebar Public Health Center, Bengkulu City. An entomological survey with a descriptive-analytic approach was conducted from January to March 2023 across five neighborhoods (RTs). A total of 100 houses and 189 water containers were examined using the House Index (HI), Container Index (CI), Breteau Index (BI), and Larval Free Index (ABJ). Adult mosquitoes were collected using resting collection and human landing catch methods. The relationship between environmental factors and larval presence was analyzed using the chi-square test (p<0.05). Of the 100 houses examined, 73 (73%) were positive for larvae, and 148 of 189 containers (78.3%) contained Aedes aegypti larvae. The highest infestation was recorded in RT 23, with HI 93.3%, CI 89.3%, BI 223.3%, and ABJ 6.7%, indicating a very high transmission risk. Aedes aegypti dominated adult mosquito collections (73.8%) compared to Aedes albopictus (26.2%). Statistical analysis showed significant associations between larval presence and uncovered water containers (p=0.004), poor waste disposal (p=0.021), and the absence of regular source reduction activities (p=0.001). The Sawah Lebar area exhibited high larval infestation and adult Aedes aegypti density, indicating a substantial risk of dengue transmission. Vector control should be strengthened through the implementation of Integrated Vector Management (IVM), emphasizing community participation in “3M Plus” practices, regular larval surveillance, environmental sanitation improvement, and intersectoral collaboration to ensure sustainable dengue prevention.